TINJAUAN TATA CARA PENOBATAN GELAR PANGULU NAN BAROMPEK DI KECAMATAN PANGEAN KABUPATEN KUANTAN SINGINGI (Jurnal Ilmu-Ilmu Sejarah, Budaya Dan Sosial ( LENTERA ), 2014)
The existence of customs procedures Gelar Pangulu Nan Barompek coronation inMalay society still exist, it is because one is still there satunnya hereditary appointment made bythe Malay community, the existence of the indigenous poorly understood most young people, theexistence of procedures for the coronation Gelar Pangulu Nan Barompek most young peoplehave a positive response means that the existence of such a custom as evidence that the persistenceof the indigenous people. Along with the development of the times most of the next generationbegan to be influenced by cultures from the outside like western culture and no assimilation withother cultures such as the presence of some people who is married to another tribe, of course itwill affect their custom.Key word : The existence of customs procedures, Gelar Pangulu Nan Barompek